Modeling – Imaginative Descriptions of Real Things: Learning About Historical Musical Instrument-Making Practices from New Technologies - Simon Waters (Music & Science)
Historical musical instrument studies, particularly when framed as organology, have tended to focus on the physical specifics of individual instruments. This article starts from a position in which musical instruments are thought of as a nexus of information: of history of course, of materials certainly, but most of all of ideas. In addition to providing new types of material evidence, digital technologies afford new opportunities for gathering, representing, and interpreting information that might have a considerable impact on our understanding of historical data. Contemporary technologies of modeling and data comparison afford approaches to the interpretation of, for example, the output and goals of a particular workshop, maker, or city that suggest that the study of multiple instruments may be instructive and valuable. Working from a larger data set potentially allows for both greater accuracy and greater subtlety of interpretation. This article will examine both the broad implications of such methodological change and the practical ramifications of learning from modeling multiple instruments.